Determination of certain biological characteristics of the pistachio seed wasp, Eurytoma plotnikovi Nik. (Hymenoptera, Eurytomidae), for its natural enemies in South East Anatolia, Turkey - Karadag S.; Sarpkaya K.; Usanmaz H.; Bengü Sahan Y.; Konukoglu F. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
The project was conducted in pistachio orchards in Gaziantep in 2011-2013. The purpose of the study was to determine biological characteristics of pistachio seed wasp, Eurytoma plotnikovi Nik. (Hymenoptera, Eurytomidae). Fruits infested with the pest were placed in cages in January in orchard. The cages were checked weekly starting in the first week of April. After the first adult emergence in the orchard in Gaziantep, daily monitoring was initiated. First and maximum adult emergence times and adult emergence period were determined in orchard. According to examination of the fruits in the orchard in Gaziantep in July in 2011 and 2013, it was determined that the pest pupates within fruits and later leaves the fruit as an adult. During the study, pupa period, adult lifespan, male/female ratio and host range of the pest in Southeastern Anatolia were determined.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)